2016
DOI: 10.1111/jth.13234
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantitative D‐dimer to exclude pulmonary embolism: a prospective cohort management study

Abstract: EssentialsIt is not known if D-dimer testing alone can safely exclude pulmonary embolism (PE). We studied the safety of using a quantitative latex agglutination D-dimer to exclude PE in 808 patients. 52% of patients with suspected PE had a negative D-dimer test and were followed for 3 months. The negative predictive value of D-dimer testing alone was 99.8%, suggesting it may safely exclude PE.Summary. Background: Strategies are needed to exclude pulmonary embolism (PE) efficiently without the need for imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 12 publications
(14 reference statements)
1
19
3
Order By: Relevance
“…The strengths of our study include its prospective outcome design and collection of data, standardized assessment, including the same D‐dimer assay in all patients, and no losses to follow‐up in the group with negative D‐dimer results who did not undergo CUS. Additionally, the DVT prevalence of 19% in our study is comparable to that in other similarly designed diagnostic studies . This relatively high prevalence decreases the likelihood of a low failure rate resulting from a low prevalence, which may arise as a result of the lower diagnostic threshold seen in recent times .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The strengths of our study include its prospective outcome design and collection of data, standardized assessment, including the same D‐dimer assay in all patients, and no losses to follow‐up in the group with negative D‐dimer results who did not undergo CUS. Additionally, the DVT prevalence of 19% in our study is comparable to that in other similarly designed diagnostic studies . This relatively high prevalence decreases the likelihood of a low failure rate resulting from a low prevalence, which may arise as a result of the lower diagnostic threshold seen in recent times .…”
Section: Discussionsupporting
confidence: 78%
“…To our knowledge, only two other prospective outcome studies have evaluated D‐dimer testing as a stand‐alone test for excluding VTE , and, as far as we know, ours is the only recent study to do so for DVT. The previous studies found similar overall negative predictive values of 99.3% and 99.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This does not accord with the recommended diagnostic algorithm, but nevertheless is not uncommon in clinical practice . It was recently suggested that D‐dimer (< 0.75 mg L −1 FEU) could be used without previous assessment of clinical pre‐test possibility to exclude PE ; however, this could not be verified in a meta‐analysis . It is noteworthy, with respect to the high sensitivities observed in the present cohort of mixed clinical probability, that the false negative results observed in the study were minor thromboses (i.e.…”
Section: Discussioncontrasting
confidence: 60%
“…A negative D‐dimer result can exclude the diagnosis of VTE without further testing, but only if the sensitivity of the test is high (>98%) . However, high sensitivity comes at the cost of specificity.…”
Section: D‐dimer Testing For Diagnosis Of Dvt and Pementioning
confidence: 99%